Cholecalciferol Effects on Lipid Profile of Experimental Animals: A Scoping Review - Dea Anenta Veonika; Budiyanti Wiboworini; Muthmainah Muthmainah (Universitas Sebelas Maret, 2024)
Vitamin D is an essential nutrient that has various beneficial effects on the human body. The results of cholecalciferol supplementation are varied, and there has yet to be a comprehensive review regarding its effect on animal models. Therefore, this scoping review aims to summarize the evidence regarding the effect of cholecalciferol (vitamin D3) supplementation on the lipid profiles of animal subjects. PubMed, Scopus, and DOAJ were searched for original research articles published until 2022. Studies were included if they were experimental studies, cholecalciferol was used as a supplement, and the changes in the lipid profile were analyzed. A total of 260 articles were collected, of which 250 articles were excluded, and 10 articles were included for qualitative synthesis. All studies used oral routes to supplement cholecalciferol with various doses and duration ranging from several weeks to several months. Most studies reported reduced lipid parameters in serum or organ-specific animals supplemented with cholecalciferol. As conclusion, cholecalciferol reduces lipid content in animal subjects and may have a beneficial effect on populations with metabolic diseases such as diabetes and dyslipidemia. Further research is required to explore the mechanism of how cholecalciferol affects the lipid profiles of experimental animals.